Transnational corporations as financial groups. (1st July 2011) - Claude Serfati,
Abstract : Whilst the 2008 crisis provided evidence of the strong (not to say devastating) interrelations between production and finance, giving a boost to the 'financialisation' approach, there is a need, forty years after the initial research on transnational corporations (TNCs), to re-explore the nature of these organisations. Issues that require investigation include the reshaping of international trade and production, the close interactions between non-financial TNCs and financial (bank and non-bank) TNCs, the development of global networks, and the strength of the relationships entertained by most of these companies with 'their' governments. A basic hypothesis of this paper, which is focused on non-financial TNCs, is that they cannot only be defined by the fact that they are bigger and more internationalised than other firms. The paper argues that, on the contrary, they constitute a category of their own, based upon a centralisation of financial assets and a specific organisational structure (with the core role held by the holding company). TNCs, organised and structured as groups of enterprises, are a locus for a global valorisation of capital, where productive and financial valorisation are closely intertwined. In the context of a global macro-economic regime of accumulation dominated by finance capital, financial logic takes on a preeminent role in the strategies of TNCs. Unfettered deregulation of financial markets and a multiplication of financial innovations (products and institutions) have given a further boost to the transformation of TNCs, which can be defined as financial groups with industrial activities.